Biomedical Informatics Training at the University of Wisconsin-Madison - Severtson, D. J.; Pape, L.; Page, C. D., Jr.; Shavlik, J. W.; Phillips, G. N.; Brennan, P. Flatley (Yearbook of Medical Informatics, 2007)
The purpose of this paper is to describe biomedical informatics training at the University of Wisconsin-Madison (UW Madison).We reviewed biomedical informatics training, research, and faculty/trainee participation at UW-Madison.There are three primary approaches to training 1) The Computation & Informatics in Biology & Medicine Training Program, 2) formal biomedical informatics offered by various campus departments, and 3) individualized programs. Training at UW-Madison embodies the features of effective biomedical informatics training recommended by the American College of Medical Informatics that were delineated as: 1) curricula that integrate experiences among computational sciences and application domains, 2) individualized and interdisciplinary cross training among adiverse cadre of trainees to develop key competencies that he or she does not initially possess, 3) participation in research and development activities, and 4) exposure to a range of basic informational and computational sciences.The three biomedical informatics training approaches immerse students in multidisciplinary training and education that is supported by faculty trainers who participate in collaborative research across departments. Training is provided across a range of disciplines and available at different training stages. Biomedical informatics training at UW-Madison illustrates how a large research University, with multiple departments across biological, computational and health fields, can provide effective and productive biomedical informatics training via multiple bioinformatics training approaches.
Keywords: Academic training; training programs; informatics; biomedical informatics